2019
DOI: 10.1002/cam4.1879
|View full text |Cite
|
Sign up to set email alerts
|

Risk of newly detected infections and cervical abnormalities in adult women seropositive or seronegative for naturally acquired HPV‐16/18 antibodies

Abstract: Background Infections with human papillomavirus (HPV) types 16 and 18 account for ~70% of invasive cervical cancers but the degree of protection from naturally acquired anti‐HPV antibodies is uncertain. We examined the risk of HPV infections as defined by HPV DNA detection and cervical abnormalities among women >25 years in the Human Papilloma VIrus Vaccine Immunogenicity ANd Efficacy trial's (VIVIANE, NCT00294047) control arm. Methods Serum anti‐HPV‐16/18 antibodies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…‘cryptic, persistent, and reversible infection of cells’ [ 56 ], rather than true eradication [ 54 57 58 ]. Data regarding immunity following such ‘cleared’ natural infections is inconsistent [ 50 59 60 61 62 ], but it is likely that natural infection, perhaps particularly among younger women [ 63 ], offers a modest degree of protection against type-specific, clinically apparent or DNA-detectable, reinfection [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…‘cryptic, persistent, and reversible infection of cells’ [ 56 ], rather than true eradication [ 54 57 58 ]. Data regarding immunity following such ‘cleared’ natural infections is inconsistent [ 50 59 60 61 62 ], but it is likely that natural infection, perhaps particularly among younger women [ 63 ], offers a modest degree of protection against type-specific, clinically apparent or DNA-detectable, reinfection [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Young women (15–25 years) enrolled in the control arms of the Costa Rica Vaccine Trial and the PATRICIA Trial who had naturally acquired HPV 16 or HPV 18 seropositivity at baseline had partial protection against subsequent HPV 16 or HPV 18 incident HPV DNA detection, and ASC-US or worse Pap results, compared with women who were seronegative [ 29 ]. Adult women in the control group of the VIVIANE Trial who were seropositive for HPV 16 at baseline also had evidence of partial protection; however, little-to-no protection was observed among those who were seropositive for HPV 18 at baseline [ 30 ]. In an analysis of young women (16–26 years) from three 4vHPV vaccine clinical trials who were HPV DNA‒negative but seropositive to a specific HPV type (6/11/16/18) at baseline, subsequent cervical or external genital disease related to one of the 4vHPV types during follow-up (approximately 40 months) was observed in some women in the placebo arm, whereas no cases of subsequent disease were observed in vaccinated women [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been discussed whether the development of HPV antibodies (and more generally an HPV infection) in early childhood protects from HPV infection or HPV associated diseases in later life [ 62 , 77 , 78 ]. Naturally acquired HPV antibodies provide protection against subsequent cervical HPV infections [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally acquired HPV antibodies provide protection against subsequent cervical HPV infections [ 79 ]. However, the effect of naturally acquired infections on immunity seems to be modest and type-specific, as the effect was only observed for HPV-16 infections [ 78 , 79 ]. Rodriguez et al [ 80 ] showed that type-specific HPV infections may reappear and may lead to precancerous lesions in previously exposed individuals, even though the risk was low.…”
Section: Discussionmentioning
confidence: 99%